Iranian EFL teachers' reflective practices and self-efficacy: Exploring possible relationships. (April 2017) - Moradkhani, Shahab; Raygan, Ali; Moein, Mohammad Sadegh
Abstract: Although reflective practice has been promoted as a means to enhance teaching, there is little empirical evidence to demonstrate its influence on improving teaching quality. To address this significant gap, the present study examines the relationship between EFL teachers' reflective practices and self-efficacy. Research has demonstrated the positive impact of self-efficacy on various dimensions of teachers' practices. It was thus assumed that understanding how self-efficacy can change in L2 teachers as a result of their reflective practices can shed light on the role of reflection in improving teachers' performance. Data were collected from 102 Iranian EFL teachers through a survey and follow-up interviews. The results of correlational analysis showed that, save for critical reflection, all the other reflection subscales had significant positive relationships with teachers' self-efficacy. The results of multiple regression also revealed that metacognitive reflection was the only predictor of teachers' self-efficacy. Analysis of the interview data, on the other hand, indicated how reflection subscales contribute to teachers' self-efficacy through one of the four main sources, namely mastery experience, vicarious experience, verbal persuasion, and physiological/emotional arousal. In line with these findings, a list of best reflective practices that are conducive to improving EFL teachers' self-efficacy is suggested.